EFFICACY OF ANTIOXIDANT WITH ALOE VERA GEL VERSUS INTRA-LESIONAL STEROIDS IN THE MANAGEMENT OF ORAL SUBMUCOUS FIBROSIS - A PROSPECTIVE COMPARATIVE STUDY - Tahir, Muhammad; Abbas, Asim; Nawaz, Faiz Ul Hassan; Raza, Mohsin; Rafique, Atif; Niazi, Muhammad Sohail Babar (Pakistan Armed Forces Medical Journal, 2021)
Objective: To compared efficacy of alpha lipoic acid (antioxidant medication) and aloe vera gel together versus intralesional steroids (hydrocortisone) in management of oral submucous fibrosis by evaluating post treatment clinical features of mouth opening and burning sensation. Study Design: A prospective comparative study. Place and Duration of Study: Department of ENT, Combined Military Hospital, Malir Karachi, from Jul 2018 to Mar 2020. Methodology: Twenty-eight patients were involved in the research and were distributed into two groups, I and II. Alpha lipoid acid with aloe vera gel was given in group I and hydrocortisone was given in group II. Burning sensation and mouth opening were recorded both at start and at monthly interval later on for three consecutive months. The data collected were statistically analyzed by using SPSS-22. Results: A significant lessening in burning sensation (p<0.001) and improvement in mouth opening were noticed in both groups. However, comparison between alpha lipoic acid with aloe vera gel group versus hydrocortisone group showed almost similar results. Conclusion: Alpha lipoic acid and aloe vera gel can significantly improve oral submucous fibrosis clinically. So, these can be utilized as an alternative option in cases where intralesional steroid is poorly tolerated or is contraindicated.